Molecular evidence for historical presence of knock-down resistance in Anopheles albimanus, a key malaria vector in Latin America - Lol, Juan C (BioMed Central, 2013)
BACKGROUND: Anopheles albimanus is a key malaria vector in the northern neotropics. Current vector control measures in the region are based on mass distributions of long-lasting insecticidal nets (LLINs) and focal indoor residual spraying (IRS) with pyrethroids. Resistance to pyrethroid insecticides can be mediated by increased esterase and/or multi-function oxidase activity and/or mutations in the voltage-gated sodium channel gene. The aim of this work was to characterize the homologous kdr region of the voltage-gated sodium channel gene in An. albimanus and to conduct a preliminary retrospective analysis of field samples collected in the 1990’s, coinciding with a time of intense pyrethroid application related to agricultural and public health insect control in the region. METHODS: Degenerate primers were designed to amplify the homologous kdr region in a pyrethroid-susceptible laboratory strain (Sanarate) of An. albimanus. Subsequently, a more specific primer pair was used to amplify and sequence the region that contains the 1014 codon associated with pyrethroid resistance in other Anopheles spp. (L1014F, L1014S or L1014C). RESULTS: Direct sequencing of the PCR products confirmed the presence of the susceptible kdr allele in the Sanarate strain (L1014) and the presence of homozygous-resistant kdr alleles in field-collected individuals from Mexico (L1014F), Nicaragua (L1014C) and Costa Rica (L1014C). CONCLUSIONS: For the first time, the kdr region in An. albimanus is described. Furthermore, molecular evidence suggests the presence of kdr-type resistance in field-collected An. albimanus in Mesoamerica in the 1990s. Further research is needed to conclusively determine an association between the genotypes and resistant phenotypes, and to what extent they may compromise current vector control efforts.